To solve the equation \(-x - 3 = x + 3\) using algebra tiles, we can follow these steps:
-
Rearrange the equation: Move all \(x\) terms to one side and constant terms to the other. For this, we can add \(x\) to both sides and add 3 to both sides.
\[ -x + x - 3 = x + x + 3 \quad \Rightarrow \quad -3 = 2x + 3 \]
Now, subtract 3 from both sides:
\[ -3 - 3 = 2x + 3 - 3 \quad \Rightarrow \quad -6 = 2x \]
-
Solve for \(x\): Now divide both sides by 2:
\[ x = \frac{-6}{2} = -3 \]
Thus, the value of \(x\) when solving the equation \(-x - 3 = x + 3\) is:
\[ x = -3 \]